Investigate the fermented coconut dregs as an alternative protein source in fish feeding - Maul Hayati, Yusoff (2025)
Focusing on fermented coconut dregs, the research helps to solve the pressing need for environmentally friendly with cost effectiveness substitutes in the fish meal industry by advancing the formulation of fermented coconut dregs added with the fish waste. The purpose to investigate the fermented coconut dregs using two types of microbes which are EM4 and Yeast at different temperature to produce a high protein yield in fish feed. The coconut dregs and fish waste undergo drying process and grinding into the powder. The protein content was checked for raw coconut dregs and fish waste. Next is the fermentation process with different temperature 25°C and 30°C for 3 days. After that, the protein content will analysed using Bradford Assay. The higher protein content of fermented coconut dregs proceeds for fish feed formulation. For fish feed formulation using 100%, 70%, 50% and 30% w/w of coconut dregs combined with 30%, 50% , 70% and 100% w/w waste of the fish. The combination of 50g fermented coconut dregs and fish waste mixed with 10ml tapioca solutions and 5 g vitamin premix. The ingredients were made in pellets form and dried in oven. The dry pellets were packed in airtight plastic and stored at a room temperature. Each sample were analysed the nutrient content such as protein, carbohydrate, lipid, fiber, ash and moisture.